Assessment and affects hamstrings contracture on the formation of posture defects in children of preschool age - Kucharczuk-Kopycińska, Magda; Krajewski, Stanisław; Krajewska, Małgorzata (Journal of Education, Health and Sport, 2016)
Purpose. The main aim of the paper is analysis connection between hamstrings contracture and fault posture. Methods. Examination covered a group of 40 children aged 4-6 from nonpublic kindergarten “Buziaczek” in Bydgoszcz. The study was divided into two parts. The first part included: evaluation of child’s figure, analysis of specified anthropometric points and identification of posture defects in particular areas of child’s body. The second part of study involved tests: "the end of the toe" and "fingers-floor" and measurement of hip joint’s range of mobility. Results. Executed tests shown that 47,5% from examined group of children have fault posture. Occurrence of hamstrings contracture, which was diagnosed in 40%, disrupts pelvis balance causing oblique position of pelvis. Conclusion. 1. Posture faults are major problem in our population. During examination near half of the group possessed at least one of the fault posture. 2. Hamstrings contracture disrupts pelvis balance causing oblique position of pelvis. Further it leads to increase frequency of fault posture. 3. Proper rehabilitation can prevent hamstring contracture, in advance prevents also occurrence of fault posture. 4. Rehabilitation study, in which analysis of specified anthropometric points and a few functional tests will be a component, can detect and correct diagnose fault posture among children.